2-year results of neoadjuvant chemotherapy for upper urinary tact transitional cell carcinoma - Siriboonrid, Satit; Karnjanatharayont, Sarayuth; Binsri, Nattapong; Reungpoca, Poonkiat (Insight Urology, 2019)
Objective: To determine whether neoadjuvant chemotherapy has any benefit in comparison to the initial surgical procedure in patients with a high-risk disease. Material and Method: Retrospective review of patients who received neoadjuvant chemotherapy followed by surgery from 2014-2017 (study group), compared to a matched cohort who underwent radical nephroureterectomy with bladder cuff excision as the first step of treatment in the same period (control group). The Fisher exact, Wilcoxon rank-sum and Kaplan-Meier methods were used. The log-rank test and Cox proportional hazards model were used to evaluate the association of these two outcomes with patients, treatment, and tumor characteristics in univariate and multivariate models. Result: Of 35 patients, 15 were in the study group and 20 in the control group. The neoadjuvant systemic therapy group had an improved overall survival (OS) and disease specific survival (DSS) in the early 2-year follow-up protocol (2-year OS and DSS was 80.2% and 90.1% in the study group, versus 57.6% in the control group). In multivariate analyses the study group had a lower risk of mortality (OS hazard ratio 0.42 [p=0.035]; DSS hazard ratio 0.19 [p=0.006]). Conclusion: Neoadjuvant with systemic therapy improves the survival of highrisk patients with upper urinary tract transitional cell carcinoma in a matched historical cohort of patients treated with initial radical nephroureterectomy with bladder cuff excision.